Design and docking of novel series of hybrid xanthones as anti-cancer agent to target human DNA topoisomerase 2-alpha (Bangladesh Journal of Pharmacology, 2014)
Topoisomerase (topo) IIα is a homodimeric protein catalyzes topological vicissitudes by adding or by soothing super coiling transpiration, occurs in human DNA during DNA replication as an outcome chromosome segregation and condensation occurs during meiosis I and recombination. To prevent the cleavage and religation activity we administered novel hybrid substituted Xanthone series of drugs. The toxicity prediction showed outstanding results which impetus to study its anticancer activities by targeting topoisomerase (topo) IIα. We developed the homology model of the topoisomerase (topo) IIα due to the unavailability of 3D structure in the Protein Data Bank. Structural assessment of the modeled protein and confirmed the quality of the model. The ligands were docked using Autodock4.2 software and binding energy was reported. The compound XM9, XN2, XM7, XLNU and XNS scored lowest binding energy and highest binding affinity. The interaction sites and the hydrogen bond were observed.